Foresight@CGIAR Workshop Report - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
This report captures discussions and key highlights from the Foresight@CGIAR workshop (https://cas.cgiar.org/isdc/meetings-and-events/foresight-cgiar) that took place on 13 November 2018 at the University of Washington, Seattle.